Frequency Adjustment of Microelectromechanical Cantilevers using Electrostatic Pull Down - Kafumbe, S. M. M.; Burdess, J. S.; Harris, A. J. (Journal of Micromechanics and Microengineering, 2005)
In this paper, a new way of actively tuning the resonant frequency of vibrating microelectromechanical devices by electrostatically adjusting the length of the resonating structure is explored. Variations in micromachining processes cause submicron differences in the size of fabricated micromachined devices, which lead to frequency variations in resonators. For radio frequency (RF) applications where high frequency selectivity and low noise frequency manipulation are key performance issues, micromachined resonators need to output a fixed frequency if they are to replace current off-chip, passive devices. This motivates the investigation of post-fabrication techniques that compensate for fabrication defects and errors, and shift the resonant frequency to its designed value. A simple universal analytical model has been developed to investigate the different states a cantilever undergoes during pull-in due to an applied voltage. The beam's natural frequencies throughout these states have been plotted. It is shown that the frequency can be changed by a factor of 4 during pull down, and thereafter increased proportionally with actuation provided an initial minimum voltage was applied.
Keywords: Frequency; microelectromechanical; electrostatic